A Review of Cybersecurity Element in Fraud Prevention and Detection Mechanisms (Open International Journal of Informatics, 2021)
Fraud is highly alarming in all sectors, and it is also seen as problematic globally. Although relevant bodies and individuals have carried out efforts in combating fraud, it appears that fraud in its various forms is a problem that is still increasing in recurrence and severity. As a result, organizations need to equip themselves with effective prevention and detection mechanisms. Furthermore, these prevention and detection mechanisms need to take into account the latest technology, which is related to cybersecurity. Cybersecurity is one of the recent areas of national and global security concerns of the 21st century. By addressing cybersecurity, organizations will thrive in a digital economy in which secured cyberspace is available for them to operate effectively. Thus, this article proposes enhanced fraud prevention and detection mechanism from the COSO framework to mitigate frauds, including cyber-attacks. Furthermore, this study also presents insights into future research work.
Keywords: fraud prevention; fraud detection; COSO; cybersecurity; public sector